Warmonger : Vladimir Putin's imperial wars - Bellamy, Alex J., 1975- (Agenda Publishing, 2023)
Ukraine is the latest of Putin's wars of aggression following Chechnya, Georgia, Crimea and Syria. This book examines each external military intervention to show how Russia rebuilt itself after the 1990s, how it embraced Putinism and an imperial vision through a series of bloody conflicts.